The September six and the struggle for the soul of Mormonism - Patterson, Sara M. (Signature Books, 2023)
"In the single month of September 1993, the Church of Jesus Christ of Latter-day Saints excommunicated or disciplined six of its members. These six individuals-some of them intellectuals, some activists, and some both-were soon dubbed the "September Six." In The September Six and the Struggle for the Soul of Mormonism, Sara M. Patterson challenges readers to think more deeply about the events of that month and the era in which they unfolded. Patterson argues that the clever alliterative phrase "September Six" masks our ability to see that what happened that month was part of a much broader, decades-long cultural and theological debate over the nature of the church and its restoration narrative. During those decades the institutional church invested in and policed a purity system, expecting believers to practice doctrinal, familial, and bodily purity. Dissenters within the institution pushed back, imagining instead a vision of the Restoration that embraced personal conscience, truth-seeking and telling, and social egalitarianism at its core. Both sides were profoundly shaped by the cultural milieu that surrounded them. What happened in September 1993 continues to echo in the church today, having lasting effects on the institution, its believers, and the broader culture"--